Medidas atípicas do art. 139, IV, do CPC/2015 como técnica de efetivação da tutela - Pontes, Janaina Martins (2021)
The use of adequate procedural tools, such as atypical measures in the fulfillment of obligations, including monetary ones, is part of the fundamental right to effective protection and the guarantee of access to justice. Effectiveness is a principle, an end to be reached. The choice of the executive measures must pass through the postulate of proportionality (adequacy, necessity, and proportionality in the strict sense). Effectiveness and efficiency are complementary; the latter requires a view beyond the process, studying the behavior of the actors and the costs of achieving social welfare, beyond the individual case. In the quest for effectiveness, Brazilian legislation has allowed the opening of executive measures. It is important to determine whether the measures provided for in article 139, IV, (coercive, mandatory, inductive and subrogation measures) are sanctions; whether the patrimonial nature of the execution interferes with the personal nature of the coercions; whether art. 139, IV, applies to extrajudicial execution titles; whether the reasoned application in each concrete case, of the use of atypical measures, with attention to the prohibition of excess and to proportionality, makes it possible for them to be used in a non-subsidiary manner; whether there is a need for correlation between the measure and the performance; whether the adversary proceeding may be deferred or how the measure can be objected. In any case, there should be no subjective, objective, or temporal exorbitance. One of the biggest problems evidenced in the study of jurisprudence on the matter is the lack of adequate reasoning of the decisions. This research aims to contribute in this area, so that there may be democratic legitimacy in the use of atypical measures as a way to enforce the law